STUDIES ON THE EFFECT OF SOLVENT ON THE THERMODYNAMICS AND KINETIC REACTIVITY OF GENETIC VARIANTS OF HUMAN ERYTHROCYTE GLUCOSE-6-PHOSPHATE DEHYDROGENASE WITH G6P (1984)
The characterization of a new variant G6PD, "Mould", has been evaluated in terms of the kinetics and thermodynamics of the binding of G6P to the new enzyme. This enzyme in comparison with G6PD B, is a new variant associated with a slow electrophoretic mobility and a slightly higher red cell G6PD activity. The variation of the kinetic and thermodynamic parameters with pH are however similar suggesting that the structural locus is not part of the binding site for G6P, but away from it. Comparison of the properties of the Mould enzyme with other known G6PD variants found in West Africa has also established the fact that the Mould enzyme is a new sporadic variant in the region. Negative cooperativity was observed for the binding of G6P to the B and Mould G6PDs. Previous kinetic data on G6P binding had given normal Michealian kinetics due to the concentration range of G6P utilized. kmG6P(2), the Km for the high affinity state of the enzyme was found to be similar to the previously determined KmG6P, implying that kinetic measurements had previously been determined at concentrations where binding will be only at the high affinity site for G6P binding on the enzyme. Since G6PD dissociates to the inactive monomer at' high G6P concentrations, the observed negative cooperativity was therefore associated with the probable mechanism by which dissociation of the-enzyme to the inactive form is prevented by the enzyme changing to a conformation with a lower affinity for G6P, The thermodynamic and kinetic functions of the G6P binding reactions have also been determined for G6PD B in water-glycerol mixtures, water, and D(2)0. In the presence of glycerol, the observed sigmoid kinetics was abolished. This behaviour is probably due to the de-formation of one of the G6P binding sites, due to pertubations of protein hydration in the presence of glycerol. Log V(max) is a linear function of dielectric constant and surface tension max: while V(max) is a linear function of viscosity. These correlations show a strong dependence of V(max) on the properties of the bulk solvent. Motive type compensation has been observed, implicating the existence of "linkage process" in G6PD reactions. For the experiments in water and D(2)0, anomalous behaviour was observed for the kinetic and thermodynamic functions of the enzyme at the temperature of maximum density for water (4.0°C) and D(2)0 (11,0°C) Correllation of V(max) and K(m) values of the enzyme with temperature, and therefore mass composition of the solvents showed that these parameters are dependent on the mass composition. Linear dependence of on viscosity of water was observed until at 4.0°C, where there was a discontinuity. Km and V(max) were also strongly dependent on the internal pressure of the two solvents. All these observations do therefore suggest that the catalytic properties of the G6PD enzyme are dependent on the intrinsic properties of the solvent in which it functions, implying that the solvent plays an important role in the catalysis of the enzyme.